Androgen receptor as a prognostic biomarker and therapeutic target in uterine leiomyosarcoma - Baek, Min-Hyun; Park, Jeong-Yeol; Park, Yangsoon; Kim, Kyu-Rae; Kim, Dae-Yeon; Suh, Dae-Shik; Kim, Jong-Hyeok; Kim, Yong-Man; Kim, Young-Tak; Nam, Joo-Hyun (Journal of gynecologic oncology, 2018)
To investigate the expression of androgen receptor (AR) and its correlation with disease status and survival outcome in uterine leiomyosarcoma with other hormone receptors. The medical records and paraffin blocks of 42 patients were reviewed. The immunohistochemical expression of AR, estrogen receptor (ER), progesterone receptor (PR), gonadotropin releasing hormone (GnRH), and cytochrome P450, family 19, subfamily A, polypeptide 1 (CYP19A1) were assessed using tissue microarray. In total, AR expression was observed in 11 patients (26.2%). International Federation of Gynecology and Obstetrics (FIGO) stage and AR were independent factors for disease-free survival (DFS) in multivariate regression analysis (odds ratio [OR]=5.8; 95% confidence interval [CI]=1.2-28.4 and OR=0.2; 95% CI=0.05-0.90; p=0.029 and 0.032, respectively). There were no deaths in the AR expression group, whereas the 5-year overall survival (OS) was 54.8% in the no expression group (p=0.014). Co-expression of ER and/or PR with AR was associated with significantly better 5-year DFS and OS than those with negative AR (72.7% vs. 28.6% and 100% vs. 64.3%; p=0.020 and 0.036, respectively). AR may be an independent prognostic marker regardless of ER/PR. AR can be a potential prognostic biomarker in uterine leiomyosarcoma.